Gestão da informação no arquivo geral da UFRN: fluxo e tratamento dos processos de aposentadoria de 1965 a 2002 - Medeiros, Maria Luzinete de (2017)
This paper investigates information and information flows management at General Archive of Universidade Federal do Rio Grande do Norte (UFRN). The baseline is the retirement processes, which precede Sistema Integrado de Patrimônio, Administração e Contratos (SIPAC), created in 2003. Theoretical foundation is about information and information flows management in organizations, besides information flow at General Archive, where retirement processes preceding SIPAC are handled. It also considers flow models and emphasizes the Access to Information Law - LAI - (Law 12 527/2011), since every public archive must meet its requirements relating to archival documental management, documental typology and custodial and post-custodial paradigm. We focus on the relevance of handling and preserving the paper supports of damaged retirement processes under the General Archive guard. In Methodology, we do a qualitative approach and action research strategy, using data collecting instruments such as documentary survey, participating observation, semi-structured interview and quiz. The research subjects are the General Archive first director, archive active public servants, some agents from Personnel Administration Department and an assistant for technical support. To analyze data, we use content analysis. For that purpose, a pilot project was elaborated; being composed by 20 retirement processes under General Archive custody, from 1965 to 2002, which are still not registered in SIPAC system. As a result, to the treatment and conservation of supports it suggests improve documents flow by cleaning, and registering in the SIPAC system. Related to the keeping documents, it suggests a better packing model to preserve physical processes.